Welcoming Faith of Tennyson and the Robust Optimism of Browning In Matthew Arnold’S Works: Exploring the Influence of Arnold's Moral Ailments and Pessimism on Modern Literature (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Matthew Arnold has his unique,distinguished place in Victorian literature and social life. He reflects in hislife as well as in his works his excessive regard for discipline and sobrietyin taste and his cultured melancholy. Passion is a thing wanting in hiswriting, and that explains lack of enthusiasm about Arnold the creator. But hisdiagnosis of the moral ailments and his intellectual pessimism have had theirinfluence on modern literature.